Association between the C-reactive protein-albumin-lymphocyte index and incident depression in patients with chronic obstructive pulmonary disease: a prospective cohort study from the UK biobank - Yushan Shi; Xianhai Chen; Yan Wang (Frontiers in Medicine, 2026)
Background Depression is a prevalent and underrecognized comorbidity in chronic obstructive pulmonary disease (COPD) that worsens outcomes. The C-reactive protein–albumin–lymphocyte (CALLY) index, a composite immune-nutritional biomarker, has demonstrated prognostic value in various chronic conditions, but its prospective association with incident depression in COPD remains unexplored. Methods This prospective cohort study included 40,200 UK Biobank participants with baseline COPD. Cox proportional hazards regression was used to estimate the association between the CALLY index and incident depression, with progressive adjustment across five models. Restricted cubic spline (RCS) curves and two-segment Cox regression was applied to characterize non-linear associations and identify inflection points. Subgroup and sensitivity analyses were conducted to assess robustness. Results During a mean follow-up of 13.1 ± 2.8 years, 2,059 incident depression events occurred. In the fully adjusted model, each one-standard deviation (SD) increment in ln-CALLY was associated with a 7% lower risk of depression (HR = 0.93, 95% CI: 0.88–0.97, P = 0.002). The highest quartile exhibited an 18% risk reduction vs. the lowest (HR = 0.82, 95% CI: 0.72–0.95, P = 0.007). RCS analysis revealed a significant L-shaped relationship ( P for non-linearity = 0.022). Threshold effect analysis identified an inflection point at CALLY = 17.75; below this threshold, each one-unit increase was associated with a 5% risk reduction (HR = 0.95, 95% CI: 0.90–0.99, P = 0.037), whereas above the threshold the association was non-significant. A nominally significant age interaction was observed ( P = 0.017), though this did not survive Bonferroni correction for multiple testing (adjusted threshold P < 0.007). Sensitivity analyses including Fine-Gray competing risk models yielded consistent results. Conclusions In COPD patients, the CALLY index exhibits a significant L-shaped association with incident depression risk, characterized by a pronounced protective effect below the identified threshold and a risk plateau above it. These findings suggest that the CALLY index may serve as a clinically accessible tool for depression risk stratification, particularly in younger COPD patients, although the age-specific effect requires confirmation in future studies.